Central Banks’ Trade-offs between Multiple Objectives and Analyses of Inflation Stability - Zeng, Ruohan (International Journal of Global Economics and Management, 2024)
This paper examines the challenges and strategies faced by central banks in weighing the multiple objectives of economic growth, full employment, price stability and financial stability. It first analyses the importance of the objectives for the economy and their interrelationships, with particular attention to the determinants of inflation stability and the effectiveness of monetary policy. Next, the role of the Taylor rule, central bank independence, transparency and communication strategies in policy making is discussed. Future research directions include the economic impact of globalisation and digitalisation, the role of central banks under climate change, and the challenges and opportunities of technological innovations for policy decision-making. Through comprehensive analyses and policy recommendations, this paper aims to provide central banks with guidance on achieving stable and sustainable economic growth and promoting market confidence and expectation management.